Binder for non-aqueous electrolyte battery, electrode mixture, electrode, and non-aqueous electrolyte battery
By using a multi-stage polymer binding agent in the battery, combining segment A with low glass transition temperature and segment B with high melting point, the problem of insufficient flexibility and endurance of the battery material layer is solved, and the stability and high performance of the material layer during winding are achieved.
Patent Information
- Application Number
- JP2024154353
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-06
- Filing Date
- 2024-09-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-06
AI Technical Summary
It is difficult to form a battery material layer with sufficient flexibility and endurance, especially during the winding of the battery, the electrode material layer faces double stresses of twisting and tension.
A multi-stage polymer is used as the binding agent for the battery, which comprises a segment (Segment A) with a glass transition temperature below 25°C and a segment (Segment B) with a melting point above 50°C to improve the flexibility and endurance of the electrode material layer.
By using a multi-stage polymer binding agent, the formed electrode material layer exhibits significant flexibility and endurance during the winding process, avoiding cracks and detachment of the material layer and improving the overall performance of the battery.
Smart Images

Figure 2025037856000001 
Figure 2025037856000002 
Figure 2025037856000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a binder for a nonaqueous electrolyte battery, an electrode mixture, an electrode, and a nonaqueous electrolyte battery. [Background technology]
[0002] Patent Document 1 describes a slurry for an electrode mixture for a lithium secondary battery, which contains an electrode active material (A), a binder (B), and fluororubber particles (C).
[0003] Patent Document 2 describes a binder containing a fluorine-containing polymer, the fluorine-containing polymer having polymerization units based on vinylidene fluoride and polymerization units based on a monomer having an amide group (-CO-NRR' (R and R' are the same or different and each represents a hydrogen atom or an alkyl group which may have a substituent)) or an amide bond (-CO-NR"- (R" represents a hydrogen atom, an alkyl group which may have a substituent, or a phenyl group which may have a substituent)), and having a solution viscosity of 10 to 20,000 mPa s.
[0004] Patent Document 3 describes a binder for batteries that contains a fluorine-containing copolymer, the fluorine-containing copolymer containing a repeating unit (a) based on vinylidene fluoride and a repeating unit represented by the general formula (b1): -(CH2-CFRf 1 )-(wherein, Rf 1 is a straight-chain or branched-chain fluorinated alkyl group or fluorinated alkoxy group having 1 to 12 carbon atoms, and when the number of carbon atoms is 2 or more, an oxygen atom may be contained between the carbon atoms. 2 )-(wherein, Rf 2is a straight-chain or branched-chain fluorinated alkyl group or fluorinated alkoxy group having 1 to 12 carbon atoms, and when the carbon number is 2 or more, an oxygen atom may be contained between the carbon-carbon atom.), and in the fluorine-containing copolymer, a molar ratio of the repeating unit (a) to the repeating unit (b) ((a) / (b)) is 95 / 5 to 5 / 95. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2011 / 002097 [Patent Document 2] JP 2013-219016 A [Patent Document 3] International Publication No. 2022 / 039260 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present disclosure is to provide a binder for a nonaqueous electrolyte battery that can form an electrode material layer having excellent flexibility and toughness. [Means for solving the problem]
[0007] According to the present disclosure, there is provided a binder for non-aqueous electrolyte batteries, which contains a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a binder for a nonaqueous electrolyte battery, which is capable of forming an electrode material layer having excellent flexibility and toughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.
[0010] A wound nonaqueous electrolyte battery is manufactured by sandwiching a separator between a positive electrode and a negative electrode and winding them. When winding, bending stress is also applied to the electrode material layer of the electrode, so the binder used to form the electrode material layer is required to have properties that can provide an electrode material layer that is excellent in flexibility and can withstand bending stress. Therefore, Patent Document 3 proposes a binder that contains a fluorine-containing copolymer containing a repeating unit (a) having a specific structure and a repeating unit (b) having a specific structure in an extremely limited molar ratio as a binder that can form an electrode material layer that exhibits sufficient flexibility.
[0011] The electrode material layer formed using the binder described in Patent Document 3 has sufficient flexibility to prevent cracking even when wound while being tightened. On the other hand, in some manufacturing methods of wound batteries, a separator is sandwiched between the positive electrode and the negative electrode, and they are wound while being applied with a certain tension. When such a manufacturing method is used, not only bending stress but also tension is applied to the electrode material layer. The present inventors have found that a battery showing high performance can be manufactured by imparting not only flexibility but also toughness to the electrode material layer used in such a manufacturing method.
[0012] The binder for nonaqueous electrolyte batteries according to the present disclosure was developed in consideration of such current circumstances, and by using the binder for nonaqueous electrolyte batteries according to the present disclosure, an electrode material layer having excellent flexibility and toughness can be formed.
[0013] In the present disclosure, the flexibility and toughness of the electrode material layer can be confirmed, for example, by performing a three-point bending test on an electrode including the electrode material layer. An electrode material layer of an electrode having a small maximum test force measured by the three-point bending test can be said to have excellent flexibility. Also, an electrode material layer of an electrode having a large half-width measured by the three-point bending test can be said to have excellent toughness. The half-width can be determined as the peak width at half the stress of the peak stress by drawing a curve with the stroke of the autograph on the horizontal axis and the stress on the vertical axis using the results of the three-point bending test of the electrode.
[0014] That is, according to the present disclosure, there is provided a binder for nonaqueous electrolyte batteries (hereinafter, sometimes referred to as a first binder for nonaqueous electrolyte batteries) containing a polymer including a segment A having a glass transition temperature of 25°C or less and a segment B having a melting point of 50°C or more.
[0015] The present disclosure also provides a binder for nonaqueous electrolyte batteries containing a polymer, the polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount of 5 mass% or less at 25°C (hereinafter, sometimes referred to as a second binder for nonaqueous electrolyte batteries).
[0016] In the present disclosure, the non-aqueous electrolyte means a liquid non-aqueous electrolyte, and is distinguished from solid electrolytes such as polymer electrolytes and inorganic solid electrolytes.
[0017] First, the configuration of the first binder for nonaqueous electrolyte batteries will be described in detail.
[0018] 1. First binder for non-aqueous electrolyte battery The first binder for nonaqueous electrolyte batteries contains a polymer including a segment A and a segment B. As long as the polymer includes a segment A and a segment B, the polymer may include another segment having a different structure from the segments A and B.
[0019] (Polymer segment A) Segment A has a glass transition temperature of 25° C. or lower. The glass transition temperature of segment A is preferably 0° C. or lower, more preferably −5° C. or lower, and even more preferably −10° C. or lower. Since the first binder for nonaqueous electrolyte batteries contains a polymer including segment A having a glass transition temperature, an electrode material layer having excellent flexibility can be formed.
[0020] The glass transition temperature can be determined by obtaining a DSC curve using a differential scanning calorimeter (DSC822e, Mettler Toledo, or X-DSC7000, Hitachi High-Tech Science) by cooling 10 mg of a sample to -75°C and then heating at 20°C / min, and determining the glass transition temperature as the temperature at the intersection of an extension of the baseline before and after the second-order transition of the DSC curve and a tangent to the inflection point of the DSC curve.
[0021] The heat of fusion of the segment A is preferably less than 5 J / g, more preferably less than 3 J / g, and even more preferably less than 2 J / g, because this can further improve the flexibility of the electrode material layer.
[0022] The heat of fusion can be calculated from the magnitude of the melting peak (ΔH) of the endothermic curve obtained by heating a sample from 30° C. to 220° C. at a rate of 10° C. / min using a differential scanning calorimetry (DSC) device. When a polymer does not show a clear melting peak, the polymer has no heat of fusion, that is, the heat of fusion of the polymer is 0 J / g.
[0023] Segment A may be a segment that does not exhibit a distinct melting point.
[0024] Segment A preferably contains a fluorine-containing monomer unit because it can improve the electrolyte resistance of the electrode material layer. The fluorine-containing monomer that can constitute segment A is not particularly limited as long as it is a monomer containing a fluorine atom, and examples thereof include vinylidene fluoride [VdF], trifluoroethylene, tetrafluoroethylene [TFE], hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, vinyl fluoride, a monomer that gives a repeating unit represented by general formula (b1) described later, and a monomer that gives a repeating unit represented by general formula (b2) described later.
[0025] The content of the fluorine-containing monomer unit in Segment A is preferably 50 mol % or more, more preferably 90 mol % or more, and even more preferably 99 mol % or more, and is preferably 100 mol % or less, and may be 100 mol %, based on all monomer units constituting Segment A.
[0026] Segment A may further contain a non-fluorine-containing monomer unit. Examples of the non-fluorine-containing monomer include ethylene, propylene, and alkyl vinyl ether. The content of the non-fluorine-containing monomer unit is preferably 0 to 50 mol%, more preferably 0 to 10 mol%, and even more preferably 0 to 1 mol%, based on the total monomer units constituting segment A, and may be 0 mol%.
[0027] Segment A may further contain units based on a monomer having a reactive group such as a cyano group, a carboxyl group, an alkoxycarbonyl group, I, Br, -CHOH, a carbon-carbon double bond, etc. The content of units based on a monomer having a reactive group is preferably 0 to 50 mol %, more preferably 0 to 10 mol %, and even more preferably 0 to 1 mol %, relative to all monomer units constituting segment A, and may be 0 mol %.
[0028] In the present disclosure, the content of each monomer unit can be measured by NMR.
[0029] Segment A preferably contains at least a VdF unit or a TFE unit as a fluorine-containing monomer unit, and more preferably contains at least a VdF unit. When segment A contains a VdF unit, the glass transition temperature of segment A can be easily adjusted to a desired range, and the flexibility of the electrode material layer can be further improved. Furthermore, when segment A contains a VdF unit, the solvent solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide can be improved.
[0030] The content of VdF units in segment A is preferably 99 to 15 mol%, more preferably 94 mol% or less, even more preferably 88 mol% or less, still more preferably 82 mol% or less, particularly preferably 80 mol% or less, more preferably 22 mol% or more, even more preferably 50 mol% or more, still more preferably 60 mol% or more, and particularly preferably 70 mol% or more, based on all monomer units constituting segment A.
[0031] It is more preferable that segment A contains at least one selected from the group consisting of a VdF unit and a repeating unit represented by any one of the following formulas, since this can further improve the flexibility of the electrode material layer and can further improve the solvent solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide: Formula:-CF2-CF[-CF3]- General formula (b1):-CH2-CFRf 1 - (In the formula, Rf 1 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms. General formula (b2):-CHF-CHRf2 - (In the formula, Rf 2 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms.
[0032] The content of at least one unit selected from the group consisting of repeating units represented by any of the above formulas in Segment A is preferably 1 to 85 mol%, more preferably 6 mol% or more, even more preferably 12 mol% or more, still more preferably 18 mol% or more, particularly preferably 20 mol% or more, more preferably 78 mol% or less, even more preferably 50 mol% or less, still more preferably 40 mol% or less, and particularly preferably 30 mol% or less, based on all monomer units constituting Segment A.
[0033] The repeating unit represented by the formula: -CF2-CF[-CF3]- is a repeating unit based on hexafluoropropylene. Thus, in one embodiment, segment A contains a VdF unit and a hexafluoropropylene unit.
[0034] General formula (b1):-CH2-CFRf 1 - At Rf 1 is a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms, or a linear or branched fluorinated alkoxy group having 1 to 12 carbon atoms. When the fluorinated alkyl group and the fluorinated alkoxy group each have 2 or more carbon atoms, they can contain an oxygen atom (-O-) between carbon atoms.
[0035] Rf 1 The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 1In the fluorinated alkyl group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferred that the fluorinated alkyl group does not contain any substituent other than a fluorine atom.
[0036] Rf 1 The fluorinated alkoxy group of Rf may be a partially fluorinated alkoxy group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkoxy group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 1 In the fluorinated alkoxy group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferable that the fluorinated alkoxy group does not contain any substituent other than a fluorine atom.
[0037] Rf 1 The number of carbon atoms is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and particularly preferably 1.
[0038] Rf 1 The general formula: -(Rf 11 ) m -(O) p -(Rf 12 -O) n -Rf 13 (In the formula, Rf 11 and Rf 12 Rf independently represents a linear or branched fluorinated alkylene group having 1 to 4 carbon atoms; 13 is a linear or branched fluorinated alkyl group having 1 to 4 carbon atoms, p is 0 or 1, m is an integer of 0 to 4, and n is an integer of 0 to 4).
[0039] Rf 11 and Rf 12 The fluorinated alkylene group of Rf may be a partially fluorinated alkylene group in which some of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms, or may be a perfluorinated alkylene group in which all of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms. 11 and Rf12 The fluorinated alkylene group of Rf may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom. 11 and Rf 12 may be the same or different in each occurrence.
[0040] Rf 11 Examples of the fluorinated alkylene group include, -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF2-CF2-, -CF2-CF2-CF2-CF2-CF2-, -CH(CF3)-CF2-CF2-, -CF(CF3)-CF2-CF2-, -CF2-CF2-CF2-, -C(CF3)2-CF2- and the like. Among these, perfluorinated alkylene groups having 1 or 2 carbon atoms are preferred, and -CF2- is more preferred.
[0041] Rf 12 Examples of the fluorinated alkylene group include -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF Among these, perfluorinated alkylene groups having 1 to 3 carbon atoms are preferred, and -CF2-, -CF2CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2- or -CF2-CF(CF3)- is more preferred.
[0042] Rf 13The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 13 The fluorinated alkyl group may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom (for example, a reactive functional group such as -CN, -I, or -Br).
[0043] Rf 13 Examples of the fluorinated alkyl group include, -CH2F, -CHF2, -CF3, -CH2-CH2F, -CH2-CHF2, -CH2-CF3, -CHF-CH2F, -CHF-CHF2, -CHF-CF3, -CF2-CH2F, -CF2-CHF2, -CF2-CF3, -CH2-CF2-CH2F, -CHF-CF2-CH2F, -CF2-CF2-CH2F, -CF(CF3)-CH2F, -CH2-CF2-CHF2, -CHF-CF2-CHF2, -CF2-CF2-CHF2, -CF(CF3)-CHF2, -CH2-CF2-CF3, -CHF-CF2-CF 3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CH2-CF2-CF2-CF3, -CHF-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, -CF(CF3)-CF2-CF3, -C(CF3)2-CF3, and the like are included, and among these, -CF3, -CHF-CF3, -CF2-CHF2, -CF2-CF3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, and -CF(CF3)-CF2-CF3 are preferred.
[0044] As p, 0 is preferable.
[0045] m is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. In addition, when p is 0, m is preferably 0 as well.
[0046] n is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0.
[0047] The repeating unit represented by formula (b1) is -CH2-CF[-CF3]-, -CH2-CF[-CF2CF3]-, -CH2-CF[-CF2CF2CF3]-, -CH2-CF[-CF2CF2CF2CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CHF-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CF2-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CF(CF3)-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CH(CF3)-CF2-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CF(CF3)-CF2-CF3]-, -CH2-CF[-OCF2OCF3]-, -CH2-CF[-OCF2CF2CF2OCF3]-, -CH2-CF[-CF2OCF2OCF3]-, -CH2-CF[-CF2OCF2CF2CF2OCF3]-, or -CH2-CF[-O-CF2-CF3]- is preferred, -CH2-CF[-CF3]-, or -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CHF-CF3]-, is more preferred.
[0048] General formula (b2):-CHF-CHRf 2 - At Rf 2is a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms, or a linear or branched fluorinated alkoxy group having 1 to 12 carbon atoms. When the fluorinated alkyl group and the fluorinated alkoxy group each have 2 or more carbon atoms, they can contain an oxygen atom (-O-) between carbon atoms.
[0049] Rf 2 The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 2 In the fluorinated alkyl group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferred that the fluorinated alkyl group does not contain any substituent other than a fluorine atom.
[0050] Rf 2 The fluorinated alkoxy group of Rf may be a partially fluorinated alkoxy group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkoxy group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 2 In the fluorinated alkoxy group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferable that the fluorinated alkoxy group does not contain any substituent other than a fluorine atom.
[0051] Rf 2 The number of carbon atoms is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and particularly preferably 1.
[0052] Rf 2 The general formula: -(Rf 21 ) m -(O) p -(Rf 22 -O) n -Rf 23 (In the formula, Rf 21 and Rf 22Rf independently represents a linear or branched fluorinated alkylene group having 1 to 4 carbon atoms; 23 is a linear or branched fluorinated alkyl group having 1 to 4 carbon atoms, p is 0 or 1, m is an integer of 0 to 4, and n is an integer of 0 to 4.
[0053] Rf 21 and Rf 22 The fluorinated alkylene group of Rf may be a partially fluorinated alkylene group in which some of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms, or may be a perfluorinated alkylene group in which all of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms. 21 and Rf 22 The fluorinated alkylene group of Rf may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom. 21 and Rf 22 may be the same or different in each occurrence.
[0054] Rf 21 Examples of the fluorinated alkylene group include, -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF2-CF2-, -CF2-CF2-CF2-CF2-CF2-, -CH(CF3)-CF2-CF2-, -CF(CF3)-CF2-CF2-, -CF2-CF2-CF2-, -C(CF3)2-CF2- and the like. Among these, perfluorinated alkylene groups having 1 or 2 carbon atoms are preferred, and -CF2- is more preferred.
[0055] Rf 22Examples of the fluorinated alkylene group include -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF Among these, perfluorinated alkylene groups having 1 to 3 carbon atoms are preferred, and -CF2-, -CF2CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2- or -CF2-CF(CF3)- is more preferred.
[0056] Rf 23 The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 23 The fluorinated alkyl group may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom (for example, a reactive functional group such as -CN, -I, or -Br).
[0057] Rf 23Examples of the fluorinated alkyl group include, -CH2F, -CHF2, -CF3, -CH2-CH2F, -CH2-CHF2, -CH2-CF3, -CHF-CH2F, -CHF-CHF2, -CHF-CF3, -CF2-CH2F, -CF2-CHF2, -CF2-CF3, -CH2-CF2-CH2F, -CHF-CF2-CH2F, -CF2-CF2-CH2F, -CF(CF3)-CH2F, -CH2-CF2-CHF2, -CHF-CF2-CHF2, -CF2-CF2-CHF2, -CF(CF3)-CHF2, -CH2-CF2-CF3, -CHF-CF2-CF 3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CH2-CF2-CF2-CF3, -CHF-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, -CF(CF3)-CF2-CF3, -C(CF3)2-CF3, and the like are included, and among these, -CF3, -CHF-CF3, -CF2-CHF2, -CF2-CF3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, and -CF(CF3)-CF2-CF3 are preferred.
[0058] As p, 0 is preferable.
[0059] m is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. In addition, when p is 0, m is preferably 0 as well.
[0060] n is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0.
[0061] The repeating unit represented by formula (b2) is -CHF-CH[-CF3]-, -CHF-CH[-CF2CF3]-, -CHF-CH[-CF2CF2CF3]-, or -CHF-CH[-CF2CF2CF2CF3]-, is preferred, -CHF-CH[-CF3]- is more preferred.
[0062] In particular, it is preferable that segment A contains VdF units and 2,3,3,3-tetrafluoropropene units. By containing VdF units and 2,3,3,3-tetrafluoropropene units in segment A, the flexibility of the electrode material layer can be further improved and an electrode mixture having excellent viscosity stability can be obtained. In addition, the solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide can be improved.
[0063] The content of 2,3,3,3-tetrafluoropropene units in Segment A is preferably 1 to 85 mol%, more preferably 6 mol% or more, even more preferably 12 mol% or more, still more preferably 18 mol% or more, particularly preferably 20 mol% or more, more preferably 78 mol% or less, even more preferably 50 mol% or less, still more preferably 40 mol% or less, and particularly preferably 30 mol% or less, based on all monomer units constituting Segment A.
[0064] In one embodiment, segment A may be formed by a 2,3,3,3-tetrafluoropropene / VdF copolymer or a 2,3,3,3-tetrafluoropropene / VdF / TFE copolymer.
[0065] In the 2,3,3,3-tetrafluoropropene / VdF copolymer, the composition (mol %) of 2,3,3,3-tetrafluoropropene units / VdF units is preferably (18 to 40) / (82 to 60), and more preferably (20 to 30) / (80 to 70).
[0066] In the 2,3,3,3-tetrafluoropropene / VdF / TFE copolymer, the composition (mol %) of 2,3,3,3-tetrafluoropropene units / VdF units / TFE units is preferably (18 to 40) / (81 to 25) / (1 to 35), and more preferably (20 to 40) / (75 to 30) / (5 to 30).
[0067] In one embodiment, segment A contains 2,3,3,3-tetrafluoropropene units and VdF units, and the content of monomer units other than 2,3,3,3-tetrafluoropropene units and VdF units is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, even more preferably 0 to 1 mol%, still more preferably 0 to 0.1 mol%, and particularly preferably 0 mol%, based on the total monomer units constituting segment A. The content of 2,3,3,3-tetrafluoropropene units and the content of VdF units may be within the above-mentioned ranges.
[0068] (Polymer segment B) Segment B has a melting point of 50° C. or higher. The melting point of segment B is preferably 90° C. or higher, more preferably 140° C. or higher, and preferably 240° C. or lower, more preferably 220° C. or lower, and further preferably 200° C. or lower. The first binder for nonaqueous electrolyte batteries contains a polymer including segment B having a melting point in addition to segment A having a glass transition temperature, and therefore can form an electrode material layer that is excellent in flexibility and toughness.
[0069] The melting point can be determined by using a differential scanning calorimetry (DSC) device to raise the temperature of a sample from 30° C. to 220° C. at a rate of 10° C. / min, and measuring the temperature at the peak of the endothermic curve obtained.
[0070] Typically, the melting point of segment B is the same as the melting point of the first polymer. Therefore, by measuring the melting point of the first polymer, the melting point of segment B in the first polymer can be determined.
[0071] The heat of fusion of segment B is preferably 5 J / g or more, more preferably 10 J / g or more, even more preferably 30 J / g or more, still more preferably 35 J / g or more, and is preferably 90 J / g or less, more preferably 60 J / g or less, and even more preferably 55 J / g or less, because this can further improve the flexibility and toughness of the electrode material layer.
[0072] The heat of fusion can be calculated from the magnitude of the melting peak (ΔH) of the endothermic curve obtained by heating a sample from 30° C. to 220° C. at a rate of 10° C. / min using a differential scanning calorimetry (DSC) device.
[0073] Segment B preferably contains a fluorine-containing monomer unit because it can improve the oxidation resistance and electrolyte resistance of the electrode material layer. The fluorine-containing monomer that can constitute segment B is not particularly limited as long as it is a monomer containing a fluorine atom, and examples thereof include vinylidene fluoride [VdF], trifluoroethylene, tetrafluoroethylene [TFE], hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, and vinyl fluoride.
[0074] The content of the fluorine-containing monomer unit in Segment B is preferably 50 mol % or more, more preferably 90 mol % or more, even more preferably 99 mol % or more, and preferably 100 mol % or less, based on all monomer units constituting Segment B.
[0075] Segment B may further contain a non-fluorine-containing monomer unit. Examples of the non-fluorine-containing monomer include ethylene, propylene, and alkyl vinyl ether. The content of the non-fluorine-containing monomer unit is preferably 0 to 50 mol%, more preferably 0 to 10 mol%, and even more preferably 0 to 1 mol%, based on the total monomer units constituting segment B, and may be 0 mol%.
[0076] Segment B may further contain a unit based on a monomer having a polar group, such as a carbonyl group-containing group, an epoxy group, a hydroxy group, a sulfonic acid group, a sulfate group, a phosphate group, an amino group, an amide group, or an alkoxy group.
[0077] Examples of monomers having a polar group include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinyl acetic acid (3-butenoic acid), 3-pentenoic acid, 4-pentenoic acid, 3-hexenoic acid, and 4-heptenoic acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonic acid esters such as dimethyl methylidene malonate; and vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether. carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylate esters such as acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxyethyl phthalate, acryloyloxypropyl succinate, and methacryloyloxyethyl phthalate; monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester; and the like.
[0078] It is preferable that segment B contains at least VdF units as fluorine-containing monomer units. By containing VdF units in segment B, the melting point of segment B can be easily adjusted within a desired range, the toughness of the electrode material layer can be further improved, and an electrode material layer having excellent electrolyte resistance can be formed. In addition, by containing VdF units in segment B, the solvent solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide can be improved.
[0079] Segment B may contain, in addition to the VdF unit, other monomer units other than the VdF unit. The other monomers may be either fluorine-containing or non-fluorine-containing monomers, and are preferably fluorine-containing monomers (excluding trifluoroethylene) or non-fluorine-containing monomers.
[0080] Examples of fluorine-containing monomers which can form segment B together with VdF include TFE, hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, and vinyl fluoride.
[0081] Examples of the fluorine-free monomer that can form the segment B together with VdF include ethylene and propylene.
[0082] In addition to the VdF unit, segment B may further contain a unit based on a monomer unit having a polar group such as a carbonyl group-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfate group, a phosphoric acid group, an amino group, an amide group, or an alkoxy group. Examples of the monomer having a polar group are as already mentioned.
[0083] As the other monomer capable of constituting segment B together with VdF, at least one selected from the group consisting of TFE, hexafluoropropylene, 2,3,3,3-tetrafluoropropene, and (meth)acrylic acid is particularly preferred.
[0084] The content of VdF units in segment B can further improve the toughness and electrolyte resistance of the electrode material layer and further improve the solvent solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide, and therefore is preferably 97 mol % or more, more preferably more than 99 mol %, and even more preferably 99.5 mol % or more and may be 100 mol % or less, based on the total monomer units constituting segment B.
[0085] The content of monomer units other than VdF units in segment B can further improve the toughness and electrolyte resistance of the electrode material layer and further improve the solvent solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide, and therefore is preferably 3 mol % or less, more preferably less than 1 mol %, and even more preferably 0.5 mol % or less, and may be 0 mol % or more, relative to the total monomer units constituting segment B.
[0086] In one embodiment, segment B can be formed by a VdF homopolymer containing only VdF units, or a copolymer containing VdF units and at least one other monomer unit selected from the group consisting of TFE units, hexafluoropropylene units, 2,3,3,3-tetrafluoropropene units, and (meth)acrylic acid units.
[0087] In a copolymer containing VdF units and other monomer units, the composition (mol %) of VdF units / other monomer units is preferably (97.0 to 99.9) / (3.0 to 0.1).
[0088] The polymer contained in the first binder for nonaqueous electrolyte batteries may contain another segment C having a different structure from the segments A and B, so long as the polymer contains the segments A and B.
[0089] The polymer contained in the first binder for nonaqueous electrolyte batteries may be a block copolymer containing a chain structure represented by any one of the following general formulas. General formula:AB General formula: ABA General formula: BAB General formula: ABC General formula: BAC (wherein A represents segment A, B represents segment B, and C represents segment C).
[0090] The polymer contained in the first binder for nonaqueous electrolyte batteries preferably contains a chain structure represented by general formula (1) or general formula (2), because it can form an electrode material layer having even more excellent flexibility and toughness and is easy to manufacture. General formula (1):ABA General formula (2): BAB (In the formula, A represents segment A and B represents segment B.)
[0091] As for the polymer contained in the first binder for nonaqueous electrolyte batteries, the mass ratio (A / B) of segment A to segment B is preferably 40 / 60 to 95 / 5, more preferably 50 / 50 or more, even more preferably 60 / 40 or more, and more preferably 90 / 10 or less, from the viewpoint of a balance between excellent flexibility and excellent toughness.
[0092] The number average molecular weight (polystyrene equivalent) of the polymer contained in the first binder for nonaqueous electrolyte batteries is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0093] The weight average molecular weight (polystyrene equivalent) of the polymer contained in the first binder for nonaqueous electrolyte batteries is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, still more preferably 200,000 or more, particularly preferably 500,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0094] The polymer contained in the first binder for nonaqueous electrolyte batteries is, for example, (1) A method of preparing a polymer for forming segment B by polymerizing a monomer for forming segment B in the presence of a bromine compound or an iodine compound as a chain transfer agent, and preparing a polymer for forming segment A by polymerizing a monomer for forming segment A in the presence of the polymer for forming segment B; (2) A method of preparing a polymer for forming segment A by polymerizing a monomer for forming segment A in the presence of a bromine compound or an iodine compound as a chain transfer agent, and preparing a polymer for forming segment B by polymerizing a monomer for forming segment B in the presence of the polymer for forming segment A; The above-mentioned manufacturing method can be used.
[0095] When method (1) is used, a polymer is obtained in which segment A is bonded to both ends of a polymer chain forming segment B, that is, a polymer containing a chain structure represented by general formula (1): ABA.
[0096] Furthermore, when method (2) is used, a polymer that forms segment B bonded to both ends of a polymer chain that forms segment A, that is, a polymer containing a chain structure represented by general formula (2): BAB, is obtained.
[0097] In the methods (1) and (2), a bromine compound or an iodine compound is used as a chain transfer agent. By using a bromine compound or an iodine compound, an iodine atom or a bromine atom is introduced into the polymer chain end forming one segment, and serves as a binding site for another segment.
[0098] The polymerization method using a bromine compound or an iodine compound includes, for example, a method in which emulsion polymerization is carried out in an aqueous medium under pressure in the presence of a bromine compound or an iodine compound in a substantially oxygen-free state (iodine transfer polymerization method). Representative examples of the bromine compound or iodine compound to be used include, for example, General formula: R 8 I x Br y (In the formula, x and y are each an integer of 0 to 2, and 1≦x+y≦2 is satisfied; R 8 is a saturated or unsaturated fluorohydrocarbon group or chlorofluorohydrocarbon group having 1 to 16 carbon atoms, or a hydrocarbon group having 1 to 3 carbon atoms, which may contain an oxygen atom).
[0099] Examples of iodine compounds include 1,3-diiodoperfluoropropane, 2-iodoperfluoropropane, 1,3-diiodo-2-chloroperfluoropropane, 1,4-diiodoperfluorobutane, 1,5-diiodo-2,4-dichloroperfluoropentane, 1,6-diiodoperfluorohexane, 1,8-diiodoperfluorooctane, 1,12-diiodoperfluorododecane, 1,16-diiodoperfluorohexadecane, diiodomethane, 1,2-diiodoethane, 1,3-diiodo-n-propane, CF2Br2, BrCF2CF2Br, CF3CFBrCF2Br, CFClBr2, BrCF2CFCl Br, CFBrClCFClBr, BrCF2CF2CF2Br, BrCF2CFBrOCF3, 1-bromo-2-iodoperfluoroethane, 1-bromo-3-iodoperfluoropropane, 1-bromo-4-iodoperfluorobutane, 2-bromo-3-iodoperfluorobutane, 3-bromo-4-iodoperfluorobutene-1, 2-bromo-4-iodoperfluorobutene-1, monoiodomonobromo-substituted benzene, diiodomonobromo-substituted benzene, and (2-iodoethyl) and (2-bromoethyl)-substituted benzene. These compounds may be used alone or in combination with each other.
[0100] Among these, it is preferable to use 1,4-diiodoperfluorobutane, 1,6-diiodoperfluorohexane, and 2-iodoperfluoropropane in terms of polymerization reactivity, crosslinking reactivity, availability, and the like.
[0101] In the above-mentioned production method, the polymerization of the monomer is preferably carried out by emulsion polymerization. In one embodiment, the polymerization of the monomer is carried out in the presence of a polymerization initiator, a surfactant and a solvent.
[0102] The polymerization initiator may be an oil-soluble radical polymerization initiator or a water-soluble radical initiator.
[0103] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and disec-butyl peroxydicarbonate, peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate, dialkyl peroxides such as di-t-butyl peroxide, and the like. In addition, di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluorooctanoyl) peroxide, di(ω-hydro-hexadecafluorononanoyl) peroxide, di(perfluorobutyryl) peroxide, di(perfluparyl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide, di(perfluorononanoyl) peroxide, di(ω-chloro- Representative examples of the perfluoro(or fluorochloro)acyl]peroxides include di(ω-chlorohexafluorobutyryl) peroxide, di(ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorodotriacontafluorodocosanoyl) peroxide.
[0104] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, or sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, or percarbonic acid, t-butyl permaleate, or t-butyl hydroperoxide, etc. A reducing agent such as sulfites may also be contained, and the amount used may be 0.1 to 20 times that of the peroxide.
[0105] The amount of the polymerization initiator to be added is not particularly limited, but may be added all at once, stepwise, or continuously in an amount (for example, several ppm relative to water concentration) at least to the extent that the polymerization rate does not drop significantly. The upper limit is within the range in which the heat of polymerization reaction can be removed from the equipment side.
[0106] The surfactant may be a nonionic surfactant, an anionic surfactant, a cationic surfactant, etc. The amount added (relative to the solvent) is preferably 10 ppm by mass to 20% by mass, more preferably 10 ppm by mass to 10% by mass, further preferably 10 to 5000 ppm by mass, and particularly preferably 50 to 5000 ppm by mass.
[0107] A polymerizable emulsifier may also be used as the surfactant. The polymerizable emulsifier is not particularly limited as long as it is a compound having at least one unsaturated bond and at least one hydrophilic group, and examples thereof include CH2=CFCF2OCF(CF3)CF2OCF(CF3)COONH4, CH2=CFCF2CF(CF3)OCF2CF2COONH4, and CF2=CFOCF2CF(CF3)OCF(CF3)COONH4. The amount of the emulsifier added (relative to the solvent) is preferably 10 to 5000 ppm by mass, more preferably 50 to 5000 ppm by mass.
[0108] The solvent is preferably a solvent that does not have chain transfer properties, and examples of the solvent include water, a mixture of water and a water-soluble organic solvent, and a mixture of water and a water-insoluble organic solvent.
[0109] In the polymerization of the monomer, the polymerization temperature, polymerization pressure and polymerization time may vary depending on the type of solvent and polymerization initiator, but may be -15 to 150°C, atmospheric pressure to 6.5 MPa, and 1 to 24 hours. When an oil-soluble radical polymerization initiator is used as the polymerization initiator, the polymerization temperature is preferably 30 to 95°C. When a water-soluble radical polymerization initiator is used as the polymerization initiator, the polymerization temperature is preferably 0 to 100°C, and more preferably 10 to 95°C.
[0110] When the polymerization of the monomer is carried out by emulsion polymerization, an aqueous dispersion containing the polymer is obtained. In the above-mentioned production method, the polymer in the aqueous dispersion is coagulated, washed with water, dehydrated, and dried to obtain a powder of the polymer. The coagulation can be carried out by adding an inorganic salt such as aluminum sulfate or an inorganic acid to the dispersion, by applying a mechanical shear force to the dispersion, or by freezing the dispersion.
[0111] The polymer contained in the first binder for nonaqueous electrolyte batteries can also be produced by using at least 2,3,3,3-tetrafluoropropene as a monomer according to the methods described in JP-A-53-3495 and JP-B-61-49327.
[0112] 2. Second binder for non-aqueous electrolyte battery A second binder for nonaqueous electrolyte batteries according to the present disclosure contains a polymer having a glass transition temperature and a melting point, which contains 2,3,3,3-tetrafluoropropene units and has a tetrahydrofuran extractable amount at 25° C. of 5 mass % or less.
[0113] The glass transition temperature of the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 25° C. or lower, more preferably 0° C. or lower, even more preferably −5° C. or lower, and even more preferably −10° C. or lower, and although there is no lower limit, may be −40° C. or higher. Since the second binder for nonaqueous electrolyte batteries contains a polymer having a glass transition temperature, it is possible to form an electrode material layer having excellent flexibility.
[0114] The glass transition temperature can be determined by obtaining a DSC curve using a differential scanning calorimeter (DSC822e, Mettler Toledo, or X-DSC7000, Hitachi High-Tech Science) by cooling 10 mg of a sample to -75°C and then heating at 20°C / min, and determining the glass transition temperature as the temperature at the intersection of an extension of the baseline before and after the second-order transition of the DSC curve and a tangent to the inflection point of the DSC curve.
[0115] The melting point of the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 50° C. or higher, more preferably 90° C. or higher, even more preferably 140° C. or higher, and preferably 240° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The second binder for nonaqueous electrolyte batteries has a glass transition temperature and contains a polymer having a melting point, and therefore is capable of forming an electrode material layer that is excellent in flexibility and toughness.
[0116] The melting point can be determined by using a differential scanning calorimetry (DSC) device to raise the temperature of a sample from 30° C. to 220° C. at a rate of 10° C. / min, and measuring the temperature at the peak of the endothermic curve obtained.
[0117] The tetrahydrofuran extractable amount of the polymer contained in the second binder for non-aqueous electrolyte batteries is 5% by mass or less, preferably 4% by mass or less, and more preferably 3% by mass or less. The second binder for non-aqueous electrolyte batteries contains a polymer with a tetrahydrofuran extractable amount within the above numerical range, and therefore can form an electrode material layer that is excellent in flexibility and toughness. The lower limit of the tetrahydrofuran extractable amount is not particularly limited, but may be 1% by mass or more or 2% by mass or more.
[0118] The amount of tetrahydrofuran extractables can be measured by a method in which a polymer is immersed in tetrahydrofuran at 25° C. for 24 hours, and the filtered solution is dried and solidified.
[0119] The polymer contained in the second binder for non-aqueous electrolyte batteries contains 2,3,3,3-tetrafluoropropene units. Since the second binder for non-aqueous electrolyte batteries contains 2,3,3,3-tetrafluoropropene units, it is possible to impart solvent solubility to the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide, and form an electrode material layer having excellent flexibility and toughness, and further, it is possible to obtain an electrode mixture having excellent viscosity stability, and form an electrode material layer having excellent electrolyte resistance.
[0120] The polymer contained in the second binder for nonaqueous electrolyte batteries preferably contains a fluorine-containing monomer unit (excluding 2,3,3,3-tetrafluoropropene units). By introducing the fluorine-containing monomer unit into the polymer, the glass transition temperature and melting point of the polymer can be easily adjusted, an electrode material layer having better flexibility and toughness can be formed, and an electrode mixture having better viscosity stability can be obtained, and an electrode material layer having better electrolyte resistance can be formed.
[0121] The fluorine-containing monomer capable of constituting the polymer contained in the second binder for nonaqueous electrolyte batteries is not particularly limited as long as it is a monomer other than 2,3,3,3-tetrafluoropropene and contains a fluorine atom, and examples of the fluorine-containing monomer include vinylidene fluoride [VdF], trifluoroethylene, tetrafluoroethylene [TFE], hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, and vinyl fluoride.
[0122] The fluorine-containing monomer capable of constituting the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably at least one selected from the group consisting of VdF, TFE, hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), and chlorotrifluoroethylene, more preferably at least one selected from the group consisting of VdF and TFE, and even more preferably VdF.
[0123] When the polymer contained in the second binder for nonaqueous electrolyte batteries contains a VdF unit as a fluorine-containing monomer unit, the solvent solubility of the binder in solvents such as N-methyl-2-pyrrolidone and N,N-dimethylformamide is further improved, and by using the second binder for nonaqueous electrolyte batteries, an electrode material layer having even more excellent flexibility and toughness can be formed, and further, an electrode mixture having even more excellent viscosity stability can be obtained, and an electrode material layer having even more excellent electrolyte resistance can be formed.
[0124] The content of 2,3,3,3-tetrafluoropropene units in the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 1 to 65 mol %, more preferably 5 mol % or more, even more preferably 9 mol % or more, still more preferably 12 mol % or more, particularly preferably 14 mol % or more, more preferably 62 mol % or less, even more preferably 40 mol % or less, still more preferably 32 mol % or less, and particularly preferably 24 mol % or less, based on all monomer units constituting the polymer.
[0125] The content of the fluorine-containing monomer unit in the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 99 to 35 mol %, more preferably 95 mol % or less, even more preferably 91 mol % or less, still more preferably 88 mol % or less, particularly preferably 86 mol % or less, more preferably 38 mol % or more, even more preferably 60 mol % or more, still more preferably 68 mol % or more, and particularly preferably 76 mol % or more, based on the total monomer units constituting the polymer.
[0126] The content of VdF units in the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 99 to 35 mol %, more preferably 95 mol % or less, even more preferably 91 mol % or less, still more preferably 88 mol % or less, particularly preferably 86 mol % or less, more preferably 38 mol % or more, even more preferably 60 mol % or more, still more preferably 68 mol % or more, and particularly preferably 76 mol % or more, based on all monomer units constituting the polymer.
[0127] The polymer contained in the second binder for non-aqueous electrolyte batteries may further contain a fluorine-free monomer unit. Examples of the fluorine-free monomer include ethylene, propylene, and alkyl vinyl ether. The content of the fluorine-free monomer unit is preferably 0 to 40 mol%, more preferably 0 to 8 mol%, and even more preferably 0 to 1 mol%, and may be 0 mol%, based on the total monomer units constituting the polymer.
[0128] The polymer contained in the second binder for nonaqueous electrolyte batteries may further contain units based on a monomer having a reactive group such as a cyano group, a carboxyl group, an alkoxycarbonyl group, I, Br, -CHOH, a carbon-carbon double bond, etc. The content of the units based on a monomer having a reactive group is preferably 0 to 10 mol %, more preferably 0 to 2 mol %, and even more preferably 0 to 1 mol %, based on the total monomer units constituting the polymer, and may be 0 mol %.
[0129] The polymer contained in the second binder for nonaqueous electrolyte batteries may further contain units based on a monomer having a polar group, such as a carbonyl group-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfate group, a phosphate group, an amino group, an amide group, or an alkoxy group.
[0130] Examples of monomers having a polar group include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinyl acetic acid (3-butenoic acid), 3-pentenoic acid, 4-pentenoic acid, 3-hexenoic acid, and 4-heptenoic acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonic acid esters such as dimethyl methylidene malonate; and vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether. carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylate esters such as acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxyethyl phthalate, acryloyloxypropyl succinate, and methacryloyloxyethyl phthalate; monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester; and the like.
[0131] The content of units based on monomers having a polar group is preferably 0 to 10 mol %, more preferably 0 to 2 mol %, and even more preferably 0 to 1 mol %, relative to all monomer units constituting the polymer, and may be 0 mol %.
[0132] In one embodiment, the polymer contained in the second binder for nonaqueous electrolyte batteries contains 2,3,3,3-tetrafluoropropene units and fluorine-containing monomer units (excluding 2,3,3,3-tetrafluoropropene units), and the content of monomer units other than 2,3,3,3-tetrafluoropropene units and fluorine-containing monomer units is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, even more preferably 0 to 1 mol%, still more preferably 0 to 0.1 mol%, and particularly preferably 0 mol%, based on the total monomer units constituting the polymer. The content of 2,3,3,3-tetrafluoropropene units and the content of fluorine-containing monomer units may be within the above-mentioned ranges.
[0133] In one embodiment, the polymer contained in the second binder for non-aqueous electrolyte batteries contains 2,3,3,3-tetrafluoropropene units and VdF units, and the content of monomer units other than 2,3,3,3-tetrafluoropropene units and VdF units is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, even more preferably 0 to 1 mol%, still more preferably 0 to 0.1 mol%, and particularly preferably 0 mol%, based on the total monomer units constituting the polymer. The content of 2,3,3,3-tetrafluoropropene units and the content of VdF units may be within the above-mentioned ranges.
[0134] The number average molecular weight (polystyrene equivalent) of the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0135] The weight average molecular weight (polystyrene equivalent) of the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, still more preferably 200,000 or more, particularly preferably 500,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0136] The heat of fusion of the polymer contained in the second binder for nonaqueous electrolyte batteries is preferably 1 J / g or more, more preferably 3 J / g or more, even more preferably 5 J / g or more, still more preferably 8 J / g or more, and is preferably 40 J / g or less, more preferably 30 J / g or less, and even more preferably 20 J / g or less.
[0137] In one embodiment of the polymer contained in the second binder for nonaqueous electrolyte batteries, the polymer contains two or more segments. By forming the polymer from two or more segments, the glass transition temperature and melting point of the polymer can be easily imparted and easily adjusted, and the flexibility and toughness of the electrode material layer can be further improved.
[0138] When the polymer contained in the second binder for a nonaqueous electrolyte battery contains two or more segments, the configuration of each segment can be the same as the configuration of each segment of the polymer contained in the first binder for a nonaqueous electrolyte battery. That is, the polymer contained in the second binder for a nonaqueous electrolyte battery can contain segment A and segment B like the polymer contained in the first binder for a nonaqueous electrolyte battery, and can have the same configuration as the polymer contained in the first binder for a nonaqueous electrolyte battery.
[0139] The polymer contained in the second binder for a nonaqueous electrolyte battery can be produced, for example, by the method described above as the method for producing the polymer contained in the first binder for a nonaqueous electrolyte battery.
[0140] The first binder for nonaqueous electrolyte batteries and the second binder for nonaqueous electrolyte batteries (hereinafter sometimes simply referred to as "binders for nonaqueous electrolyte batteries") may contain other polymers in addition to the above-mentioned polymers. Examples of the other polymers include fluoropolymers, polymethacrylates, polymethyl methacrylates, polyacrylonitriles, polyimides, polyamides, polyamideimides, polycarbonates, styrene rubbers, butadiene rubbers, styrene butadiene rubbers, and polyacrylic acids.
[0141] The binder for nonaqueous electrolyte batteries according to the present disclosure can be suitably used as a material for forming batteries such as secondary batteries and capacitors.
[0142] The present disclosure also relates to the use of a binder containing a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more for forming a nonaqueous electrolyte battery. The binder can be particularly suitably used for forming an electrode material layer of a nonaqueous electrolyte battery.
[0143] The present disclosure also relates to the use of a binder for forming a nonaqueous electrolyte battery, the binder containing a polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount of 5 mass% or less at 25° C. The binder can be particularly suitably used for forming an electrode material layer of a nonaqueous electrolyte battery.
[0144] The battery may be a primary battery, a storage battery (secondary battery), or a storage element. The nonaqueous electrolyte battery includes all nonaqueous electrolyte batteries that include an electrolyte and a power generation element. Examples of nonaqueous electrolyte batteries include lithium ion primary batteries, lithium ion secondary batteries, sodium ion secondary batteries, nickel-metal hydride batteries, lithium ion capacitors, and electric double layer capacitors.
[0145] The binder for nonaqueous electrolyte batteries of the present disclosure can form an electrode material layer having excellent flexibility and toughness, and is therefore suitable as a binder for use in electrodes of batteries such as secondary batteries, capacitors, etc. The binder for nonaqueous electrolyte batteries of the present disclosure can also be used as a binder for the separator coating of secondary batteries.
[0146] The binder for non-aqueous electrolyte batteries of the present disclosure may be a binder for non-aqueous electrolyte secondary batteries. In the present disclosure, the binder for non-aqueous electrolyte secondary batteries includes binders used in the positive electrode, negative electrode, and separator of non-aqueous electrolyte secondary batteries. The non-aqueous electrolyte secondary battery is preferably a lithium ion secondary battery.
[0147] 3. Electrode mixture The electrode mixture for a non-aqueous electrolyte battery of the present disclosure contains the above-mentioned binder for a non-aqueous electrolyte battery, a powder electrode material, and water or a non-aqueous solvent. The electrode mixture of the present disclosure may be an electrode mixture for a non-aqueous electrolyte secondary battery, or may be an electrode mixture for a lithium ion secondary battery. Since the electrode mixture of the present disclosure contains the above-mentioned binder for a non-aqueous electrolyte battery, it is possible to form an electrode material layer having excellent flexibility and toughness.
[0148] The electrode mixture may be a positive electrode mixture used for producing a positive electrode, or a negative electrode mixture used for producing a negative electrode. The electrode material layer formed from the electrode mixture of the present disclosure may be a positive electrode material layer or a negative electrode material layer, as long as it contains the above-mentioned battery binder and powder electrode material.
[0149] The powder electrode material is a powder electrode material used in a battery, and preferably contains an electrode active material. The electrode active material is divided into a positive electrode active material and a negative electrode active material. In the case of a lithium ion secondary battery, the positive electrode active material is not particularly limited as long as it can electrochemically absorb and release lithium ions, but a lithium composite oxide is preferable, and a lithium transition metal composite oxide is more preferable. The positive electrode active material is also preferably a lithium-containing transition metal phosphate compound. It is also preferable that the positive electrode active material is a material containing lithium and at least one transition metal, such as a lithium transition metal composite oxide or a lithium-containing transition metal phosphate compound.
[0150] The transition metal of the lithium transition metal composite oxide is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples of the lithium transition metal composite oxide include lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3, and those in which a part of the transition metal atoms that are the main components of these lithium transition metal composite oxides is replaced with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. Examples of the above-mentioned replacements include lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, lithium nickel cobalt manganese composite oxide, lithium manganese aluminum composite oxide, lithium titanium composite oxide, etc., and more specifically, LiNi 0.5 Mn 0.5 O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi0.9 Mn 0.05 Co 0.05 O2, LiMn 1.8 Al 0.2 O4, LiMn 1.5 Ni 0.5 O4, Li4Ti5O 12 , LiNi 0.82 Co 0.15 Al 0.03 O2, etc.
[0151] The transition metal of the lithium-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples of the lithium-containing transition metal phosphate compound include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main components of these lithium transition metal phosphate compounds has been substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0152] In particular, from the viewpoints of high voltage, high energy density, charge / discharge cycle characteristics, etc., LiCoO2, LiNiO2, LiMn2O4, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.33 Mn 0.33 Co 0.33 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.9 Mn 0.05 Co 0.05 O2, LiFePO4 are preferred.
[0153] As the lithium transition metal composite oxide, a lithium-nickel composite oxide is preferable, and the lithium transition metal composite oxide is represented by the general formula (7): General formula (7): Liy Ni 1-x M x O2 (In the formula, x is 0.01≦x≦0.5, y is 0.9≦y≦1.2, and M represents a metal atom (excluding Li and Ni).) Lithium-nickel composite oxides represented by the following formula are more preferable. Lithium transition metal composite oxides with a high nickel content like this are useful for increasing the capacity of secondary batteries.
[0154] In general formula (7), x is a coefficient satisfying 0.01≦x≦0.5, and since a secondary battery with a higher capacity can be obtained, it is preferable that 0.05≦x≦0.4, and more preferably 0.10≦x≦0.3.
[0155] In the general formula (7), examples of the metal atom of M include V, Ti, Cr, Mn, Fe, Co, Cu, Al, Zn, Mg, Ga, Zr, Si, etc. As the metal atom of M, transition metals such as V, Ti, Cr, Mn, Fe, Co, Cu, etc., or combinations of the above transition metals with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Mg, Ga, Zr, Si, etc. are preferred.
[0156] Lithium transition metal oxides with a high nickel content include LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.33 Mn 0.33 Co 0.33 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiNi 0.90 Mn 0.05 Co 0.05 At least one selected from the group consisting of LiNi0.82 Co 0.15 Al 0.03 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2 and LiNi 0.9 Mn 0.05 Co 0.05 More preferably, the compound is at least one selected from the group consisting of O2.
[0157] In addition, a material having a different composition from the material constituting the main positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attaching material include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.
[0158] These surface-attaching substances can be attached to the surface of the positive electrode active material by, for example, a method in which the surface-attaching substance precursor is dissolved or suspended in a solvent, added to the positive electrode active material by impregnation, and then dried; a method in which the surface-attaching substance precursor is dissolved or suspended in a solvent, added to the positive electrode active material by impregnation, and then reacted by heating or the like; a method in which the surface-attaching substance precursor is added to the positive electrode active material precursor and then calcined at the same time; or the like.
[0159] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more by mass relative to the positive electrode active material, and is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less by mass relative to the positive electrode active material. The surface-attached substance can suppress the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material, and can improve the battery life, but if the amount of attachment is too small, the effect is not fully manifested, and if it is too large, the ingress and egress of lithium ions is inhibited, which may increase the resistance.
[0160] The shape of the particles of the positive electrode active material may be agglomerated, polyhedral, spherical, elliptical, plate-like, needle-like, columnar, etc., as has been conventionally used. Among them, primary particles are aggregated to form secondary particles, and the secondary particles are preferably spherical or elliptical. Normally, in an electrochemical element, the active material in the electrode expands and contracts with charging and discharging, and the active material is easily damaged by the stress, such as broken conductive paths. Therefore, a primary particle aggregated to form a secondary particle is preferable to a single particle active material consisting of only primary particles, because it relieves the stress of expansion and contraction and prevents deterioration. In addition, spherical or elliptical particles are less oriented when forming the electrode, so that the expansion and contraction of the electrode during charging and discharging is less, and they are also more easily mixed uniformly with the conductive agent when preparing the electrode, making them preferable.
[0161] The tap density of the positive electrode active material is usually 1.3 g / cm 3 More than 1.5 g / cm, preferably 1.5 g / cm 3 More preferably, 1.6 g / cm 3 More preferably, 1.7 g / cm 3 That is all. If the tap density of the positive electrode active material is below the lower limit, the amount of dispersion medium required during the formation of the positive electrode material layer increases, and the amounts of conductive agent and binder required also increase, which may restrict the filling rate of the positive electrode active material in the positive electrode material layer and restrict the battery capacity. By using a metal composite oxide powder with a high tap density, a high-density positive electrode material layer can be formed. Generally, the higher the tap density, the more preferable it is, and there is no particular upper limit. However, if the tap density is too high, the diffusion of lithium ions in the positive electrode material layer using the nonaqueous electrolyte as a medium becomes rate-limiting, and the load characteristics may be easily deteriorated, so that the tap density is usually set to 3.5 g / cm. 3 Less than 3.3 g / cm, preferably 3.3 g / cm 3 The following is the result.
[0162] The tap density of the positive electrode active material is measured by passing it through a sieve with an opening of 300 μm and measuring the density of the material at 20 cm 3After dropping a sample into the tapping cell to fill the cell volume, tapping is performed 1,000 times with a stroke length of 10 mm using a powder density measuring device (for example, Tap Denser manufactured by Seishin Enterprise Co., Ltd.), and the density calculated from the volume and weight of the sample at that time is defined as the tap density.
[0163] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter when primary particles are aggregated to form secondary particles) is usually 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, most preferably 3 μm or more, and usually 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, most preferably 15 μm or less. If it is below the lower limit, a high bulk density product may not be obtained, and if it exceeds the upper limit, it may take time for lithium to diffuse within the particles, resulting in a decrease in battery performance, or problems such as streaking may occur when the positive electrode of the battery is produced, that is, when the active material, conductive agent, binder, etc. are slurried with a solvent and applied in a thin film. Here, by mixing two or more types of positive electrode active materials having different median diameters d50, the filling property during the production of the positive electrode can be further improved.
[0164] In the present disclosure, the median diameter d50 is measured by a known laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used as the dispersion medium for the measurement, and the measurement is performed after ultrasonic dispersion for 5 minutes with a measurement refractive index set to 1.24.
[0165] When the primary particles are aggregated to form secondary particles, the average primary particle diameter of the positive electrode active material is usually 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, and most preferably 0.1 μm or more, and usually 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which may adversely affect powder packing properties or may greatly reduce the specific surface area, resulting in a high possibility of battery performance such as output characteristics being reduced. Conversely, if the lower limit is exceeded, problems such as poor reversibility of charge and discharge may occur due to underdeveloped crystals. The primary particle diameter is measured by observation using a scanning electron microscope (SEM). Specifically, the longest intercept value of the boundary between the left and right sides of the primary particles with respect to a horizontal line is determined for any 50 primary particles in a 10,000x magnification photograph, and the average value is calculated.
[0166] The BET specific surface area of the positive electrode active material is 0.1 m 2 / g or more, preferably 0.15m 2 / g or more, more preferably 0.18m 2 / g or more, 4.0m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 1.5m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, whereas if it is larger, it is difficult to increase the tap density, and problems may easily occur in the application property when forming the positive electrode material layer.
[0167] The BET specific surface area is defined as the value measured by a surface area meter (for example, an automatic surface area measuring device manufactured by Ohkura Riken) by pre-drying a sample at 150°C for 30 minutes under a nitrogen flow, and then measuring the value by a nitrogen adsorption BET single-point method using a gas flow method, using a nitrogen-helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.
[0168] A method for producing a positive electrode active material is a method generally used for producing inorganic compounds. In particular, various methods are conceivable for producing a spherical or elliptical active material. For example, a method for dissolving or grinding and dispersing a transition metal raw material such as a transition metal nitrate or sulfate, and a raw material of other elements as necessary, in a solvent such as water, adjusting the pH while stirring to produce and recover a spherical precursor, which is dried as necessary, and then adding a Li source such as LiOH, Li2CO3, or LiNO3 and baking at a high temperature to obtain an active material; a method for dissolving or grinding a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, or oxide, and a raw material of other elements as necessary, in a solvent such as water; Examples of such a method include dispersing a precursor material in a solvent such as water, drying and molding the resulting mixture using a spray dryer or the like to form a spherical or ellipsoidal precursor, adding a Li source such as LiOH, Li2CO3, LiNO3, etc., and firing the mixture at a high temperature to obtain an active material, and also dissolving or pulverizing and dispersing transition metal raw materials such as transition metal nitrates, sulfates, hydroxides, and oxides, Li sources such as LiOH, Li2CO3, LiNO3, etc., and raw materials of other elements as necessary, in a solvent such as water, drying and molding the resulting mixture using a spray dryer or the like to form a spherical or ellipsoidal precursor, and firing the mixture at a high temperature to obtain an active material.
[0169] In the present disclosure, the positive electrode active material powder may be used alone as one type, or two or more types having different compositions or different powder properties may be used in any combination and ratio.
[0170] The negative electrode active material is not particularly limited as long as it can electrochemically absorb and release lithium ions, and examples of the negative electrode active material include carbonaceous materials, metal oxides such as tin oxide and silicon oxide, metal composite oxides, lithium alone, lithium alloys such as lithium-aluminum alloys, metals capable of forming alloys with lithium such as Sn and Si, etc. These may be used alone or in any combination and ratio of two or more.
[0171] The metal composite oxide is not particularly limited as long as it is capable of absorbing and releasing lithium, but it is preferable from the viewpoint of high current density charge / discharge characteristics that it contains titanium and / or lithium as a constituent component.
[0172] Carbonaceous materials include: (1) Natural graphite, (2) Artificial carbonaceous substances and artificial graphitic substances; carbonaceous substances {for example, natural graphite, coal-based coke, petroleum-based coke, coal-based pitch, petroleum-based pitch, or these pitches that have been oxidized, needle coke, pitch coke, and carbon materials obtained by partially graphitizing these pitches, furnace black, acetylene black, pitch-based carbon fiber, and other organic pyrolysis products; carbonizable organic substances (for example, coal tar pitch ranging from soft pitch to hard pitch, coal-based heavy oil such as carbonized liquefied oil, atmospheric residual oil, vacuum residual oil, straight-run heavy oil, cracked petroleum heavy oil such as ethylene tar produced as a by-product during the thermal decomposition of crude oil, naphtha, etc., aromatic hydrocarbons such as acenaphthylene, decacyclene, anthracene, phenanthrene, etc.; N-ring compounds such as phenazine and acridine; S-ring compounds such as thiophene and bithiophene; biphenyl, terphenyl, etc.); carbonaceous materials obtained by heat-treating the following at least once in the range of 400 to 3200°C: polyphenylene such as polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, insolubilized products of these, nitrogen-containing organic polymers such as polyacrylonitrile and polypyrrole, sulfur-containing organic polymers such as polythiophene and polystyrene, natural polymers such as cellulose, lignin, mannan, polygalacturonic acid, chitosan, and polysaccharides represented by saccharose, thermoplastic resins such as polyphenylene sulfide and polyphenylene oxide, thermosetting resins such as furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin), and carbonized products thereof, or solutions of carbonizable organic substances dissolved in low-molecular organic solvents such as benzene, toluene, xylene, quinoline, and n-hexane, and carbonized products thereof; (3) A carbonaceous material in which the negative electrode material layer is made of at least two or more carbonaceous materials having different crystallinity and / or has an interface where the carbonaceous materials having different crystallinity are in contact with each other; (4) A carbonaceous material in which the negative electrode layer is made of at least two or more kinds of carbonaceous materials having different orientations and / or has an interface where the carbonaceous materials having different orientations are in contact with each other; The material selected from the above is preferable because it has a good balance between the initial irreversible capacity and the high current density charge / discharge characteristics.
[0173] The content of the electrode active material (positive electrode active material or negative electrode active material) is preferably 40 mass % or more in the electrode mixture in order to increase the capacity of the obtained electrode.
[0174] The powder electrode material may further include a conductive agent, such as carbon blacks such as acetylene black and ketjen black, carbon materials such as graphite, carbon fibers, carbon nanotubes, carbon nanohorns, graphene, and the like.
[0175] The ratio of the powder electrode material (active material and conductive agent) to the above-mentioned battery binder in the electrode mixture is usually about 80:20 to 99.5:0.5 by mass, and is determined taking into consideration the retention of the powder components, adhesion to the current collector, and conductivity of the electrode.
[0176] At the blending ratio as described above, in the electrode material layer formed on the current collector, the above-mentioned battery binder cannot completely fill the gaps between the powder components. However, when water or a non-aqueous solvent that well dissolves or disperses the battery binder is used as the solvent, the battery binder is uniformly dispersed and becomes mesh-like in the electrode material layer after drying, and the powder components are well held, which is preferable.
[0177] The electrode mixture of the present disclosure contains water or a non-aqueous solvent. Examples of the non-aqueous solvent include nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as dioxane; and mixtures thereof.
[0178] In particular, the electrode mixture of the present disclosure preferably contains a non-aqueous solvent, from the viewpoint of excellent stability and coatability of the electrode mixture, preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N,N-dimethylacetamide, and more preferably contains N-methyl-2-pyrrolidone.
[0179] The amount of water or non-aqueous solvent in the electrode mixture is determined in consideration of the applicability to the current collector, the formability of a thin film after drying, etc. Usually, the ratio of the battery binder to the water or non-aqueous solvent is preferably 0.5:99.5 to 20:80 by mass.
[0180] In order to further improve adhesion to the current collector, the electrode mixture may further contain, for example, an acrylic resin such as polyacrylic acid, polymethacrylate, or polymethyl methacrylate, a polyimide, a polyamide, or a polyamideimide resin, a styrene rubber, a butadiene rubber, or a styrene butadiene rubber.
[0181] In order to improve the dispersion stability of the electrode slurry, a dispersant such as a resin having a surface active effect, a cationic surfactant, or a nonionic surfactant may be added to the electrode mixture.
[0182] The content of the binder for non-aqueous electrolyte batteries in the electrode mixture is preferably 0.1 to 20 mass %, more preferably 0.2 to 10 mass %, and further preferably 0.5 to 3 mass %, based on the mass of the electrode mixture.
[0183] The electrode mixture can be prepared by dispersing and mixing the powder electrode material in a solution or dispersion in which a binder for non-aqueous electrolyte batteries is dissolved or dispersed in water or a non-aqueous solvent. The resulting electrode mixture is then uniformly applied to a current collector such as a metal foil or metal mesh, dried, and pressed as necessary to form a thin layer of the electrode material on the current collector, thereby forming a thin film electrode.
[0184] In addition, the binder for non-aqueous electrolyte batteries and the powder of the electrode material may be mixed first, and then water or a non-aqueous solvent may be added to prepare the electrode mixture. Also, the binder for non-aqueous electrolyte batteries and the powder of the electrode material may be heated and melted, extruded with an extruder to prepare a thin electrode mixture, and then pasted onto a collector coated with a conductive adhesive or a general-purpose organic solvent to prepare an electrode sheet. Furthermore, a solution or dispersion of the binder for non-aqueous electrolyte batteries and the powder of the electrode material may be applied to a preformed electrode material in advance. Thus, the method of application as the binder for non-aqueous electrolyte batteries is not particularly limited.
[0185] 4. Electrode The electrode of the present disclosure contains the binder for non-aqueous electrolyte batteries described above. The electrode of the present disclosure is preferably an electrode for non-aqueous electrolyte batteries. Since the electrode of the present disclosure contains the binder for non-aqueous electrolyte batteries described above, the electrode does not crack even if the powder electrode material is thickly coated and wound and pressed to increase density, and the powder electrode material does not fall off or peel off from the current collector.
[0186] The electrode preferably comprises a current collector and an electrode material layer formed on the current collector, the electrode material layer containing the powder electrode material and the binder for non-aqueous electrolyte batteries described above. The electrode may be a positive electrode or a negative electrode, but is preferably a positive electrode.
[0187] Examples of the current collectors (positive and negative current collectors) include metal foils or metal meshes of iron, stainless steel, copper, aluminum, nickel, titanium, etc. Among these, aluminum foil is preferred as the positive current collector, and copper foil is preferred as the negative current collector.
[0188] The electrode of the present disclosure can be manufactured, for example, by the method described above. Since the electrode mixture has excellent coatability, the electrode material layer of the electrode of the present disclosure can be manufactured using the electrode mixture, whereby an electrode having a smooth, uniform, and thick electrode material layer can be easily manufactured.
[0189] 5. Nonaqueous electrolyte battery The nonaqueous electrolyte battery of the present disclosure includes the above-mentioned electrode. The nonaqueous electrolyte battery of the present disclosure is preferably a nonaqueous electrolyte secondary battery. In one embodiment of the nonaqueous electrolyte battery of the present disclosure, the battery includes a positive electrode in which a positive electrode mixture is held by a positive electrode current collector, a negative electrode in which a negative electrode mixture is held by a negative electrode current collector, and an electrolyte. In the nonaqueous electrolyte secondary battery of the present disclosure, at least one of the positive electrode and the negative electrode may be the above-mentioned electrode, and the positive electrode is preferably the above-mentioned electrode. The secondary battery is preferably a lithium ion secondary battery.
[0190] The nonaqueous electrolyte secondary battery of the present disclosure preferably further comprises a nonaqueous electrolyte. The nonaqueous electrolyte is not particularly limited, but one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroether, and fluorinated carbonate can be used. Any of the conventionally known electrolytes can be used, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, and the like can be used.
[0191] A separator may be interposed between the positive electrode and the negative electrode. As the separator, a conventional separator may be used, or a separator coated with the above-mentioned battery binder may be used.
[0192] It is also preferable to use the above-mentioned binder for non-aqueous electrolyte batteries in at least one of the positive electrode, negative electrode, and separator of a secondary battery (preferably a lithium ion secondary battery).
[0193] A film for a secondary battery made of the binder for a nonaqueous electrolyte battery described above is also one of the preferred embodiments of the present disclosure.
[0194] A laminate for a secondary battery having a substrate and a layer made of the binder for a non-aqueous electrolyte battery formed on the substrate is also one of the preferred embodiments of the present disclosure. Examples of the substrate include those exemplified as the current collector and known substrates (such as porous membranes) used for separators in secondary batteries.
[0195] The electrode of the present disclosure includes an electrode material layer having excellent flexibility and toughness, and therefore can be suitably used as an electrode for a wound-type nonaqueous electrolyte secondary battery. The nonaqueous electrolyte secondary battery of the present disclosure may be a wound-type nonaqueous electrolyte secondary battery.
[0196] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.
[0197] <1> According to a first aspect of the present disclosure, There is provided a binder for non-aqueous electrolyte batteries, which contains a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more. <2> According to a second aspect of the present disclosure, There is provided a binder for a nonaqueous electrolyte battery according to a first aspect, in which segment A has a heat of fusion of less than 5 J / g, and segment B has a heat of fusion of 5 J / g or more. <3> According to a third aspect of the present disclosure, There is provided a binder for non-aqueous electrolyte batteries according to a first or second aspect, wherein the polymer contains a chain structure represented by general formula (1) or general formula (2). General formula (1):ABA General formula (2): BAB (In the formula, A represents segment A and B represents segment B.) <4> According to a fourth aspect of the present disclosure, In the binder for non-aqueous electrolyte batteries according to any one of the first to third aspects, there is provided a binder for non-aqueous electrolyte batteries according to any one of the first to third aspects, wherein segment A of the polymer contains a fluorine-containing monomer unit. <5> According to a fifth aspect of the present disclosure, According to any one of the first to fourth aspects, there is provided a binder for a nonaqueous electrolyte battery, wherein segment A of the polymer contains a vinylidene fluoride unit. <6> According to a sixth aspect of the present disclosure, There is provided a binder for nonaqueous electrolyte batteries according to any of the first to fifth aspects, wherein segment A of the polymer contains a vinylidene fluoride unit and at least one selected from the group consisting of repeating units represented by any of the following formulas: Formula:-CF2-CF[-CF3]- Formula:-CH2-CFRf 1 - (In the formula, Rf 1 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms. Formula:-CHF-CHRf 2 - (In the formula, Rf 2 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms. <7> According to a seventh aspect of the present disclosure, In accordance with any one of the first to sixth aspects, there is provided a binder for a non-aqueous electrolyte battery, wherein segment A of the polymer contains vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units. <8> According to an eighth aspect of the present disclosure, In the binder for a nonaqueous electrolyte battery according to any one of the fifth to seventh aspects, there is provided a content of vinylidene fluoride units in segment A of the polymer relative to all monomer units constituting segment A, which is 99 to 15 mol %. <9> According to a ninth aspect of the present disclosure, In accordance with any one of the first to eighth aspects, there is provided a binder for a nonaqueous electrolyte battery, wherein segment B of the polymer contains a fluorine-containing monomer unit. <10> According to a tenth aspect of the present disclosure, According to any one of the first to ninth aspects, there is provided a binder for a nonaqueous electrolyte battery, wherein segment B of the polymer contains a vinylidene fluoride unit. <11> According to an eleventh aspect of the present disclosure, In a tenth aspect, there is provided a binder for non-aqueous electrolyte batteries, wherein a content of vinylidene fluoride units in segment B of the polymer is 97 mol % or more based on all monomer units constituting segment B. <12> According to a twelfth aspect of the present disclosure, Segment B of the polymer is Contains only vinylidene fluoride units, or Contains vinylidene fluoride units and at least one monomer unit selected from the group consisting of tetrafluoroethylene units, hexafluoropropylene units, 2,3,3,3-tetrafluoropropene units, and (meth)acrylic acid units. According to any one of the first to eleventh aspects, there is provided a binder for a nonaqueous electrolyte battery. <13> According to a thirteenth aspect of the present disclosure, In the binder for a nonaqueous electrolyte battery according to any one of the first to twelfth aspects, a mass ratio of segment A to segment B in the polymer is from 40 / 60 to 95 / 5. <14> According to a fourteenth aspect of the present disclosure, The polymer contains a chain structure represented by general formula (1) or general formula (2), General formula (1):ABA General formula (2): BAB (In the formula, A represents segment A and B represents segment B.) Segment A of the polymer is It has a glass transition temperature of -10°C or less, containing vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units in segment A being 18 to 30 mol % based on all monomer units constituting segment A, and the content of the vinylidene fluoride units in segment A being 70 to 82 mol % based on all monomer units constituting segment A, Segment B of the polymer is It has a melting point of 140 to 200°C. Segment B contains vinylidene fluoride units, and the content of the vinylidene fluoride units in Segment B is 97 mol % or more based on all monomer units constituting Segment B; The mass ratio of segment A to segment B in the polymer is 50 / 50 to 90 / 10; The weight average molecular weight of the polymer is 200,000 to 2,000,000. According to any one of the first to thirteenth aspects, there is provided a binder for a nonaqueous electrolyte battery. <15> According to a fifteenth aspect of the present disclosure, Provided is a binder for non-aqueous electrolyte batteries that contains a polymer, the polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount of 5 mass% or less at 25°C. <16> According to a sixteenth aspect of the present disclosure, In a fifteenth aspect, there is provided a binder for a non-aqueous electrolyte battery, wherein the polymer further contains a vinylidene fluoride unit. <17> According to a seventeenth aspect of the present disclosure, According to a fifteenth or sixteenth aspect, there is provided a binder for a non-aqueous electrolyte battery, wherein the polymer contains two or more segments. <18> According to an eighteenth aspect of the present disclosure, The glass transition temperature of the polymer is −10° C. or lower; The melting point of the polymer is 140 to 200°C, the polymer contains vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units being 9 to 24 mol % based on all monomer units constituting the polymer, and the content of the vinylidene fluoride units being 76 to 91 mol % based on all monomer units constituting the polymer; The polymer has a tetrahydrofuran extractable amount of 2 to 4% by mass at 25°C, The weight average molecular weight of the polymer is 200,000 to 2,000,000. According to any one of the fifteenth to seventeenth aspects, there is provided a binder for a nonaqueous electrolyte battery. <19> According to a nineteenth aspect of the present disclosure, According to any one of the first to eighteenth aspects, there is provided an electrode mixture for a non-aqueous electrolyte battery, comprising the binder for a non-aqueous electrolyte battery. <20> According to a twentieth aspect of the present disclosure, According to a nineteenth aspect, there is provided an electrode mixture for a non-aqueous electrolyte battery, further comprising a powder electrode material, and water or a non-aqueous solvent. <21> According to a twenty-first aspect of the present disclosure, According to a nineteenth or twentieth aspect, there is provided an electrode for a non-aqueous electrolyte battery, comprising an electrode material layer formed from the electrode mixture. <22> According to a twenty-second aspect of the present disclosure, According to a twenty-first aspect, there is provided a non-aqueous electrolyte battery comprising an electrode. EXAMPLES
[0198] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.
[0199] The values in the examples were measured by the following methods.
[0200] <Polymer composition> The compositions of the fluorocopolymer and PVdF were measured by solution NMR. Measurement equipment: Varian VNMRS400 Resonance frequency: 376.04 (Sfrq) Pulse width: 30° (pw = 6.8)
[0201] <Content of polar group-containing monomer units in PVdF> The content of polar group-containing monomer units (such as acrylic acid units, maleic acid, etc.) in PVdF was measured by acid-base titration of carboxyl groups. Specifically, about 0.5 g of PVdF was dissolved in acetone at a temperature of 70 - 80 °C. 5 ml of water was added dropwise under intense stirring to avoid coagulation of PVdF. Titration with an aqueous NaOH solution having a concentration of 0.1 N was carried out until complete neutralization of the acidity at a neutral transition of about -270 mV. From the measurement results, the amount of substance of the polar group-containing monomer units contained in 1 g of PVdF was determined, and the content of the polar group-containing monomer units was calculated.
[0202] <Weight-average molecular weight> Regarding the weight-average molecular weight of PVdF, it was measured by gel permeation chromatography (GPC). It was calculated from the data measured using Toso's AS-8010, CO-8020, columns (three GMHHR-H columns connected in series) and Shimadzu's RID-10A, with dimethylformamide (DMF) as the solvent flowing at a flow rate of 1.0 ml / min (reference: polystyrene). Also, regarding the weight-average molecular weight of the fluorine-containing copolymer, the molecular weight was calculated based on standard polystyrene based on the results measured by the GPC method. GPC apparatus: TOSOH HLC-8320GPC Column: 1 SuperAW-H, 3 SuperAWM-H Developing solvent: Dimethylformamide [DMF] Sample concentration: 0.05 mass% Measurement temperature: 40 °C
[0203] <Storage elastic modulus (E’)> The storage elastic modulus is the value measured at 30 °C or 60 °C by dynamic viscoelasticity measurement. A test piece with a length of 30 mm, a width of 5 mm, and a thickness of 50 - 100 μm was measured in tensile mode with a grip width of 20 mm, a measurement temperature range from -30 °C to 160 °C, a heating rate of 2 °C / min, and a frequency of 1 Hz using a dynamic viscoelasticity apparatus DVA220 manufactured by IT Measurement Control Co., Ltd.
[0204] The test piece used for measurement was prepared by dissolving PVdF in N-methyl-2-pyrrolidone (NMP) to a concentration of 10 - 20 mass%, casting the resulting solution on a glass plate, drying it at 100 °C for 12 hours, further drying it under vacuum at 100 °C for 12 hours, and then cutting the obtained film with a thickness of 50 - 100 μm into pieces with a length of 30 mm and a width of 5 mm.
[0205] <Melting point> Using a differential scanning calorimetry (DSC) apparatus, the temperature corresponding to the peak of the endothermic curve when the sample was heated from 30 °C to 220 °C at a rate of 10 °C / min was determined as the melting point.
[0206] <Glass transition temperature (Tg)> Using a differential scanning calorimeter (DSC822e manufactured by Mettler Toledo or X-DSC7000 manufactured by Hitachi High-Tech Science), a DSC curve was obtained by heating 10 mg of the sample at a rate of 20 °C / min. The temperature indicated by the intersection of the extension line of the baseline before and after the secondary transition of the DSC curve and the tangent line at the inflection point of the DSC curve was defined as the glass transition temperature.
[0207] <Heat of fusion> Using a differential scanning calorimeter (DSC822e manufactured by Mettler Toledo or X-DSC7000 manufactured by Hitachi High-Tech Science), the sample was heated from 30 °C to 220 °C at a rate of 10 °C / min, and the heat of fusion was calculated from the magnitude of the melting peak (ΔH) of the obtained endothermic curve.
[0208] <THF extraction amount> 9 g of tetrahydrofuran (THF) was added to 1 g of the polymer obtained in each Example, and the mixture was stirred using a stirrer at 25° C. After 24 hours, the solid content was filtered, the solution was dried, and the weight of the dried matter was measured to calculate the amount of extraction (the ratio (mass %) of the weight of the dried matter to the weight (1 g) of the polymer).
[0209] <Viscosity change rate of positive electrode mixture> Using a Brookfield viscometer (DV2T), the viscosity of the positive electrode mixture was measured 10 minutes after the start of the measurement under the conditions of 25°C, spindle LV-04(64), and rotation speed of 6 rpm. The viscosity change rate (X24) was calculated by the following formula from the viscosity (η0) of the positive electrode mixture measured immediately after preparation and the viscosity (η24) 24 hours after preparation of the mixture under the condition of a storage temperature of 50°C. Xn = η24 / η0 × 100 [%]
[0210] <Peel strength between positive electrode material layer and positive electrode current collector> A 1.2 cm x 7.0 cm test piece was prepared by cutting out a positive electrode with a positive electrode material layer on one side. The positive electrode material layer side of the test piece was fixed to a movable jig with double-sided tape, and then tape was applied to the surface of the positive electrode current collector. The stress (N / cm) when the tape was pulled 90 degrees at a speed of 100 mm / min was measured using an autograph. A 1 N load cell was used for the autograph.
[0211] <Maximum test force> The bending strength (3-point bending test) was measured according to a method in accordance with ASTM D790. A positive electrode with a positive electrode material layer on both sides or a negative electrode with a negative electrode material layer on both sides was cut to a size of 15 mm x 20 mm to prepare a test piece. In the 3-point bending method, the test piece was placed between the first and second points, which were spaced 10 mm apart, and the center of the test piece (the third point) was pressed with a probe in the thickness direction of the test piece at a constant speed to perform a bending property test. The force applied to the third point was measured while moving at a thickness direction speed of 5 mm / min. The maximum bending force or maximum bending strength is the maximum value of the force applied to the test piece depending on the moving distance of the probe.
[0212] <Half width> The bending strength (3-point bending test) was measured according to a method in accordance with ASTM D790. A positive electrode having a positive electrode material layer on both sides or a negative electrode having a negative electrode material layer on both sides was cut into a size of 15 mm x 20 mm to prepare a specimen. In the 3-point bending method, a specimen was placed between the first and second points, which were spaced 10 mm apart, and the center of the specimen (the third point) was pressed with a probe at a constant speed in the thickness direction of the specimen to perform a bending property test. The force applied was measured while moving at a thickness direction moving speed of 5 mm / min at the third point. The maximum bending strength (maximum bending force or maximum bending strength) is the maximum force applied to the specimen depending on the moving distance of the probe. Next, the test force of half the maximum bending strength was calculated, and the distance from the stroke at which the test force reached half the maximum bending strength when the test force increased after the start of the test to the stroke at which the test force reached half the maximum bending strength when the test force decreased after reaching the maximum test force was the half-value width. That is, a curve can be drawn with the stroke of the autograph on the horizontal axis and the stress on the vertical axis, and the peak width at a stress half the peak stress can be specified.
[0213] The following polymers were used in the examples and comparative examples.
[0214] PVdF A: VdF homopolymer Weight average molecular weight 900000 Storage modulus at 30℃: 1740MPa Storage modulus at 60℃: 1140MPa Melting point: 171°C B: VdF homopolymer Weight average molecular weight 1800000 Storage modulus at 30℃: 1820MPa Storage modulus at 60℃: 1180MPa Melting point: 171°C C: PVdF containing acrylic acid units Acrylic acid unit content: 1.0 mol% Weight average molecular weight 1100000 Storage modulus at 30℃: 1280MPa Storage modulus at 60℃: 720MPa Melting point: 161°C D: PVdF containing maleic acid units Maleic acid unit content: 0.5 mol% Weight average molecular weight 900000 Storage modulus at 30℃: 1260MPa Storage modulus at 60℃: 760MPa Melting point: 167°C E: PVdF containing CTFE units CTFE unit content: 2.4 mol% Weight average molecular weight 800000 Storage modulus at 30℃: 1250MPa Storage modulus at 60℃: 880MPa Melting point: 168°C F: PVdF containing HFP units and acrylic acid units VdF / HFP=97.5 / 2.5 (mol%) Acrylic acid unit content: 1.0 mol% Weight average molecular weight 1110000 Storage modulus at 30℃: 1080MPa Storage modulus at 60℃: 750MPa Melting point: 150℃
[0215] Production example 1 Fluorine-containing copolymer a (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) (Process 1) In a 6L stainless steel autoclave, add 4000ml of pure water, 0.8001g of CH2=CFCF2OCF(CF3)CF2OCF(CF3)COONH450% aqueous solution, and C5F 11 24.021g of COONH450% aqueous solution was added and replaced with nitrogen, then VdF was applied for slight pressure, and the temperature was adjusted to 80°C while stirring at 400 rpm. VdF was injected up to 1.64 MPa, and further VdF and 2,3,3,3-tetrafluoropropylene (R1234yf) mixed monomer with a molar ratio of 77.2 / 22.8 was injected up to 2.001 MPa. 0.16g of ammonium persulfate dissolved in 4ml of pure water was injected with nitrogen to start polymerization. When the mixed monomer reached 24g, 1.009g of 1,4-diiodoperfluorobutane was added. When the pressure dropped to 1.98MPa, the mixed monomer was increased to 2.01MPa, and this was repeated until 1020g was charged. After releasing the gas in the autoclave to 0.05MPa, heat treatment was performed for 3 hours. A 10 g sample of the dispersion in the autoclave was taken and dried to obtain a polymer with a molar ratio of VdF / R1234yf=77.6 / 22.4, a glass transition temperature of -12.5°C, and no heat of fusion.
[0216] (Process 2) After the heat treatment in step 1, the autoclave was kept at 80°C and pressurized to 2.003MPa with VdF, and 0.08g of ammonium persulfate dissolved in 4ml of pure water was pressed in with nitrogen to start polymerization. When the pressure dropped to 1.98MPa, the pressure was increased to 2.01MPa with VdF, and this was repeated until 180g was charged, at which point the gas in the autoclave was released and cooled, and 5270g of dispersion was recovered. The solid content of the dispersion was 23.83% by mass.
[0217] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1250 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=82.0 / 18.0 in molar ratio, and the content of segment B calculated from the composition was 17.2 mass%. The weight average molecular weight Mw was 1,266,000, the glass transition temperature was -12.9°C, the melting point was 160.3°C, and the heat of fusion was 8.2 mJ / mg. The amount of THF extracted was 3 mass%.
[0218] Production example 2 Fluorine-containing copolymer b (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) The same procedure as in Production Example 1 was followed, except that the amount of the mixed monomer charged in step 1 was changed from 1020 g to 900 g, and the amount of VdF charged in step 2 was changed from 180 g to 300 g, to recover 5236 g of a dispersion. The solid content of the dispersion was 24.10 mass%.
[0219] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1257 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=84.2 / 15.8 in molar ratio, and the content of segment B calculated from the composition was 28.1 mass%. The weight average molecular weight Mw was 1,206,000, the glass transition temperature was -11.0°C, the melting point was 161.1°C, and the heat of fusion was 11.0 mJ / mg. The amount of THF extracted was 3 mass%.
[0220] Production example 3 Fluorine-containing copolymer c (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) The same procedure as in Production Example 1 was followed, except that the amount of the mixed monomer charged in step 1 was changed from 1020 g to 780 g, and the amount of VdF charged in step 2 was changed from 180 g to 420 g, to recover 5252 g of a dispersion. The solid content of the dispersion was 23.74 wt%.
[0221] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1250 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=85.9 / 14.1 in molar ratio, and the content of segment B calculated from the composition was 36.0 mass%. The weight average molecular weight Mw was 1.29 million, the glass transition temperature was -11.2°C, the melting point was 161.4°C, and the heat of fusion was 17.1 mJ / mg. The amount of THF extracted was 3 mass%.
[0222] Production example 4 Fluorine-containing copolymer d (Preparation of ABA block polymer (wherein A represents segment A and B represents segment B)) (Process 1) In a 6L stainless steel autoclave, add 4000ml of pure water, 0.8003g of CH2=CFCF2OCF(CF3)CF2OCF(CF3)COONH450% aqueous solution, and C5F 11 24.014g of COONH450% aqueous solution was added and replaced with nitrogen, then VdF was slightly pressurized, and the temperature was adjusted to 80°C while stirring at 400 rpm, and VdF was pressed in up to 2.00 MPa. 0.16g of ammonium persulfate dissolved in 4ml of pure water was pressed in with nitrogen to start polymerization. When the pressure reached 24g of VdF, 1.009g of 1,4-diiodoperfluorobutane was added. When the pressure dropped to 1.98MPa, it was increased to 2.01MPa with VdF, and this was repeated until 300g was charged, after which the gas in the autoclave was released to 0.05MPa, and heat treatment was performed for 3 hours. 10g of the dispersion in the autoclave was sampled and dried to obtain a polymer whose glass transition temperature was not visible, its melting point was 161.1°C, and its heat of fusion was 44.8mJ / mg.
[0223] (Process 2) After the heat treatment in step 1, the autoclave was kept at 80°C, and the pressure was increased to 1.64MPa with VdF and 2.001MPa with a mixed monomer solution of VdF and R1234yf with a molar ratio of 77.5 / 22.5, and 0.08g of ammonium persulfate dissolved in 4ml of pure water was added with nitrogen to start polymerization. When the pressure dropped to 1.98MPa, the mixed monomer solution was increased to 2.01MPa, and this was repeated until 900g was added, at which point the gas in the autoclave was released and cooled, and 5271g of dispersion was recovered. The solid content of the dispersion was 23.80% by mass.
[0224] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1248 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=82.7 / 17.3 in molar ratio, and the content of segment B calculated from the composition was 24.1 mass%. The weight average molecular weight Mw was 1,426,000, the glass transition temperature was -10.4°C, the melting point was 160.8°C, and the heat of fusion was 10.8 mJ / mg. The amount of THF extracted was 3 mass%.
[0225] Examples 1 to 11, Comparative Examples 1 to 5 (Preparation of binder solution) A composition (binder solution) was prepared by dissolving the fluorocopolymer and PVdF in N-methyl-2-pyrrolidone (NMP) in the composition (mass ratio) in Table 1 so that the concentration of the binder (fluorocopolymer and PVdF) in the NMP solution was 7 mass%.
[0226] (Preparation of Positive Electrode Mixture) The composition obtained above was mixed with a positive electrode active material (NMC(LiNi 0.9 Mn 0.05 Co 0.05 O2)) and a conductive agent (Ketjen Black (SuperP Li, manufactured by TIMCAL)) were added and thoroughly mixed with a stirrer to prepare a positive electrode mixture. The mass ratio of the positive electrode active material, conductive agent, and binder in the positive electrode mixture was 97 / 1.5 / 1.5. The solid content in the positive electrode mixture was 74 mass%.
[0227] (Preparation of a positive electrode with a positive electrode material layer on one side) The obtained positive electrode mixture was applied to one side of a positive electrode current collector (aluminum foil with a thickness of 20 μm) in an amount of 24.5 mg / cm 2 After the NMP was completely evaporated, a pressure of 10 tons was applied twice using a roll press to produce a positive electrode including a positive electrode material layer and a positive electrode current collector.
[0228] (Preparation of a positive electrode with positive electrode material layers on both sides) The obtained positive electrode mixture was applied to both sides of a positive electrode current collector (aluminum foil with a thickness of 20 μm) in an amount of 32.0 mg / cm per side. 2 After completely volatilizing the NMP, the mixture was pressed using a roll press machine at a pressure of 7 tons to produce a positive electrode including a positive electrode material layer and a positive electrode current collector.
[0229] The evaluation results of the positive electrode mixture and the electrode are shown in Table 1.
[0230] [Table 1]
[0231] Example 12 As the negative electrode active material, 19.2 mass% of graphite-coated silicon oxide powder (powder in which the surface of silicon oxide is coated with graphite), 76.8 mass% of graphite powder, and 4.0 mass% of fluorine-containing copolymer c (7% NMP solution) as a binder were mixed, and an appropriate amount of NMP was further added to prepare a negative electrode mixture slurry. Next, this negative electrode mixture slurry was applied to both sides of a negative electrode current collector made of copper foil, and this was dried. This was cut into a predetermined electrode size, and rolled with a roll press at a pressure of 10t to produce a negative electrode in which a negative electrode material layer was formed on both sides of the negative electrode current collector. The evaluation results are shown in Table 2.
[0232] Example 13 A negative electrode was prepared in the same manner as in Example 12, except that the negative electrode active material was 48.0 mass% of graphite-coated silicon oxide powder, 48.0 mass% of graphite powder, and the binder was 0.8 mass% of PVdF A and 3.2 mass% of fluorine-containing copolymer c. The evaluation results are shown in Table 2.
[0233] Comparative Example 6 A negative electrode was produced in the same manner as in Example 12, except that polyacrylic acid (manufactured by Aldrich, weight average molecular weight 450,000) was used as the binder. The evaluation results are shown in Table 2.
[0234] Comparative Example 7 A negative electrode was produced in the same manner as in Example 13, except that styrene-butadiene rubber (TRD2001, manufactured by JSR Corporation) was used as the binder. The evaluation results are shown in Table 2.
[0235] [Table 2]
[0236] Example 14 A negative electrode was produced in the same manner as in Example 12, except that 19.2 mass % of silicon powder and 76.8 mass % of graphite powder were used as the negative electrode active material. The evaluation results are shown in Table 3.
[0237] Example 15 A negative electrode was produced in the same manner as in Example 13, except that 47.5 mass % of silicon powder and 47.5 mass % of graphite powder were used as the negative electrode active material. The evaluation results are shown in Table 3.
[0238] Comparative Example 8 A negative electrode was produced in the same manner as in Example 14, except that styrene-butadiene rubber (TRD2001, manufactured by JSR Corporation) was used as the binder. The evaluation results are shown in Table 3.
[0239] Comparative Example 9 A negative electrode was produced in the same manner as in Example 15, except that polyacrylic acid (manufactured by Aldrich, weight average molecular weight 450,000) was used as the binder. The evaluation results are shown in Table 3.
[0240]
Table 3
Claims
1. A binder for a non-aqueous electrolyte battery, comprising a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more.
2. 2. The binder for a nonaqueous electrolyte battery according to claim 1, wherein segment A has a heat of fusion of less than 5 J / g, and segment B has a heat of fusion of 5 J / g or more.
3. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein the polymer contains a chain structure represented by general formula (1) or general formula (2). General formula (1): ABA General formula (2): B-A-B (In the formula, A represents segment A and B represents segment B.)
4. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein the segment A of the polymer contains a fluorine-containing monomer unit.
5. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein the polymer segment A contains a vinylidene fluoride unit.
6. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein segment A of the polymer contains a vinylidene fluoride unit and at least one repeating unit selected from the group consisting of repeating units represented by any one of the following formulae: Formula: -CF 2 -CF[-CF 3 - Formula: -CH 2 -CFR 1 - (In the formula, Rf 1 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between the carbon atoms. Formula: -CHF-CHRR 2 - (In the formula, Rf 2 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between the carbon atoms.
7. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein the polymer segment A contains a vinylidene fluoride unit and a 2,3,3,3-tetrafluoropropene unit.
8. 6. The binder for a non-aqueous electrolyte battery according to claim 5, wherein the content of vinylidene fluoride units in the segment A of the polymer is 99 to 15 mol % based on the total monomer units constituting the segment A.
9. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein the segment B of the polymer contains a fluorine-containing monomer unit.
10. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein the segment B of the polymer contains a vinylidene fluoride unit.
11. 11. The binder for a non-aqueous electrolyte battery according to claim 10, wherein the content of vinylidene fluoride units in the segment B of the polymer is 97 mol % or more based on all monomer units constituting the segment B.
12. Segment B of the polymer is Contains only vinylidene fluoride units, or Contains vinylidene fluoride units and at least one monomer unit selected from the group consisting of tetrafluoroethylene units, hexafluoropropylene units, 2,3,3,3-tetrafluoropropene units and (meth)acrylic acid units. The binder for a nonaqueous electrolyte battery according to claim 1 or 2.
13. 3. The binder for a non-aqueous electrolyte battery according to claim 1, wherein a mass ratio of the segment A to the segment B in the polymer is from 40 / 60 to 95 / 5.
14. The polymer contains a chain structure represented by general formula (1) or general formula (2), General formula (1): ABA General formula (2): B-A-B (In the formula, A represents segment A and B represents segment B.) Segment A of the polymer is It has a glass transition temperature of −10° C. or less, containing vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units in segment A being 18 to 30 mol % based on all monomer units constituting segment A, and the content of the vinylidene fluoride units in segment A being 70 to 82 mol % based on all monomer units constituting segment A, Segment B of the polymer is It has a melting point of 140 to 200°C, Segment B contains vinylidene fluoride units, and the content of the vinylidene fluoride units in Segment B is 97 mol % or more based on all monomer units constituting Segment B; The mass ratio of segment A to segment B in the polymer is 50 / 50 to 90 / 10; The weight average molecular weight of the polymer is 200,000 to 2,000,000. The binder for a nonaqueous electrolyte battery according to claim 1 or 2.
15. A binder for non-aqueous electrolyte batteries containing a polymer, the polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount at 25° C. of 5 mass % or less.
16. The binder for a non-aqueous electrolyte battery according to claim 15, wherein the polymer further contains a vinylidene fluoride unit.
17. The binder for a nonaqueous electrolyte battery according to claim 15 or 16, wherein the polymer contains two or more segments.
18. The glass transition temperature of the polymer is −10° C. or lower; The melting point of the polymer is 140 to 200° C., the polymer contains vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units being 9 to 24 mol % based on all monomer units constituting the polymer, and the content of the vinylidene fluoride units being 76 to 91 mol % based on all monomer units constituting the polymer; The polymer has a tetrahydrofuran extractable amount of 2 to 4% by mass at 25° C.; The weight average molecular weight of the polymer is 200,000 to 2,000,000. The binder for a nonaqueous electrolyte battery according to claim 15 or 16.
19. An electrode mixture for a non-aqueous electrolyte battery, comprising the binder for a non-aqueous electrolyte battery according to claim 1 or 15.
20. 20. The electrode mixture for a non-aqueous electrolyte battery according to claim 19, further comprising a powdered electrode material, and water or a non-aqueous solvent.
21. An electrode for a non-aqueous electrolyte battery, comprising an electrode material layer formed from the electrode mixture according to claim 19.
22. A non-aqueous electrolyte battery comprising the electrode according to claim 21.
Citation Information
Patent Citations
BAB type block copolymer, preparation method, binder, positive pole piece, secondary battery and electric device
CN115286805A
Lithium secondary battery, polymer gel electrolyte, and binder for lithium secondary battery
JP1999067274A
Solid electrolyte molding body, electrode molding body, and electrochemical element
JP2000123874A
functionalized fluorinated copolymer
JP2018530662A
solid polymer electrolyte
JP2021514095A